Roquette-Pinto imortal: constituição, tratamento e usos do Arquivo Roquette-Pinto na Academia Brasileira de Letras - Souza, Juliana Amorim de (2015)
The dissertation presents an analysis of the production, custody and use of the personal papers of Edgard Roquette-Pinto, today in the permanent custody of the Brazilian Academy of Letters (ABL). The aim is to highlight the representations circulating local guard this archive, suggest the reconstitution of the holder of the relationship with your file, illuminate the various patterns of accumulation and interference that the file would be submitted as well, enabling the reflection on the effects of interference made by the researchers leading the organization, and by archivists at the time of your organization.